Analisis Penggunaan Produk Kecantikan sebagai Strategi Pemasaran Syariah dalam Keputusan Pembelian Konsumen oleh Karyawan Zahra Swalayan Kepung Kediri Perspektif Hukum Islam - Ninis Umi Rahmatin; Siti Kalimah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2021)
Islam does not prohibit the use of beauty products or cosmetics to beautify oneself. Allah loves beauty and cleanliness, and Allah loves women who are able to take care of themselves, namely keeping themselves clean and beautifying themselves with everything that is lawful. This research is a descriptive study with a qualitative approach. This type of research is empirical research. Based on the results of the research, it shows that Zahra supermarket does not make beauty products as a sharia marketing strategy, but the use of beauty products used by female employees has little influence in the field of sharia marketing strategies carried out by Zahra supermarkets in Kepung, Kediri. The marketing strategy that is carried out really prioritizes honesty and holds promos on some of the products it sells to attract consumer interest.